Taxonomic notes on desmids from the Netherlands II, with a description of six new species - van Westen, Marien C.; Coesel, Peter F. M. (Phytotaxa, 2018)
From the Netherlands, six desmid species are described as new to science: Closterium joostenii, Cosmarium abbreviatiforme, Cosmarium kouwetsii, Cosmarium spierense, Staurastrum exlooënse, and Staurastrum subcomptum. Furthermore, Closterium archerianum var. pseudocynthia is raised to species level with the name Closterium cynthiaforme. The affinity with similarly looking taxa is discussed.